Correction to: The burden of chronic diseases across Europe: what policies and programs to address diabetes? A SWOT analysis - Angela Giusti; Marina Maggini; Sofia Colaceci (BMC, 2020)
It was highlighted that in the original article [1] Fig. 2 was incorrect and the link for the Additional File was missing. This Correction article provides the correct Fig. 2 and the Additional File with its link. The original file has been updated.